2019
DOI: 10.1002/jbt.22312
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin modulates dextran sulfate sodium‐induced ulcerative colitis in rats: Targeting sphingosine kinase‐1‐ sphingosine 1 phosphate signaling pathway, mitochondrial biogenesis, inflammation, and apoptosis

Abstract: Ulcerative colitis (UC) is a chronic gastrointestinal disorder interfering with life quality. A total of 60 male Wistar rats were divided into four equal groups: Control (group I), hesperidin only (group II), UC untreated (group III), and UC treated with hesperidin (group IV). Hesperidin had modulatory effects on UC pathogenesis, which might be through alleviating colonic sphingosine phosphate phosphatase 2 messenger RNA expression and sphingosine kinase-1 levels, thus suppressing the subsequent downstream inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The antioxidants SOD and NQO-1 directly eliminate free superoxide radicals to protect against lipid peroxidation [50,51]. Previous reports of acute gut inflammation in the DSS model observed a significant increase in lipid peroxidation and reduced levels of antioxidant enzymes (NQO-1 and SOD) [18,19,[52][53][54][55][56], which were replicated in the present study. We also observed a significant reduction in MDA levels after treatment with idebenone, which is consistent with a previous report where idebenone effectively suppressed lipid peroxidation in brain mitochondria [57].…”
Section: Discussionsupporting
confidence: 87%
“…The antioxidants SOD and NQO-1 directly eliminate free superoxide radicals to protect against lipid peroxidation [50,51]. Previous reports of acute gut inflammation in the DSS model observed a significant increase in lipid peroxidation and reduced levels of antioxidant enzymes (NQO-1 and SOD) [18,19,[52][53][54][55][56], which were replicated in the present study. We also observed a significant reduction in MDA levels after treatment with idebenone, which is consistent with a previous report where idebenone effectively suppressed lipid peroxidation in brain mitochondria [57].…”
Section: Discussionsupporting
confidence: 87%
“…Studies revealed that apoptosis is a marker of active UC. [ 40,41 ] TUNEL assay showed more TUNEL‐positive cells in the DSS + DB group of male animals as compared to female animals. NLR family pyrin domain‐containing 3 (NLRP3) inflammasome, found in the intestinal epithelial cells and its downstream effector proteins, caspase‐1 and IL‐1β are responsible for intestinal inflammation.…”
Section: Discussionmentioning
confidence: 97%
“…Mitochondria are intracellular double-membrane-bound organelles that play a key role in inflammatory diseases such as rheumatoid arthritis and UC [37,38]. The maintenance of mitochondrial function might counteract the inflammation, oxidative stress, and epithelial barrier damage in colitis [39,40].…”
Section: Discussionmentioning
confidence: 99%